Managing risk in extreme environments front-line business lessons for corporates and financial institutions - Martin, Duncan (Gale virtual reference library, 2008)
Presents real-life examples of extreme situations - from epidemics to earthquakes - to showcase risk management strategies which have been tested and shown to succeed.